Hands-On Exploratory Data Analysis with R : Become an Expert in Exploratory Data Analysis Using R Packages. - Datar, Radhika (Packt Publishing, Limited, 2019)
Hands-On Exploratory Data Analysis with R puts the complete process of exploratory data analysis into a practical demonstration in one nutshell. You will understand the concepts of data analysis right from data ingestion, data cleaning, data manipulation to applying statistical techniques and visualizing hidden patterns.